2005
DOI: 10.1007/s11107-005-4530-5
|View full text |Cite
|
Sign up to set email alerts
|

Shared-Risk Logical Span Groups in Span-Restorable Optical Networks: Analysis and Capacity Planning Model

Abstract: Abstract. In an optical transport network distinct logical groups of lightwave channels between neighboring OXC nodes (called spans) may sometimes be realized over a common physical resource such as a duct or conduit, and hence share a common cause of failure. This is closely related to the concept of shared risk on individual channels or links, called SRLGs, which is relevant to pre-planned path protection schemes with shared capacity on backup paths. But when considering span-restorable networks, shared risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In [13] (see also [27,Chapter 11.4.2,) it has been shown that MSP is W [1]-hard if the parameter is the number of disjoint subsets. 2…”
Section: Parameterized Complexitymentioning
confidence: 99%
“…In [13] (see also [27,Chapter 11.4.2,) it has been shown that MSP is W [1]-hard if the parameter is the number of disjoint subsets. 2…”
Section: Parameterized Complexitymentioning
confidence: 99%
“…Various approaches to path provisioning, and more specifically routing and wavelength assignment (RWA) in optical networks containing SRLGs have been studied [11], [12], [13], [14] with the common goal of avoiding the failure of working and spare path at the same time. RWA problem can be expressed as an integer linear program.…”
Section: Related Workmentioning
confidence: 99%
“…It can also represent links that are located in the same seismic area, or radio links in access and backhaul networks subject to localized environmental conditions affecting signal transmission, or traffic jam propagation in road networks. In practice the failures are localized and very common SRLGs are star SRLGs or SRLGs verifying the star property [7] (coincident SRLGs in [5]). Under this property, a link can be affected by more than one risk but all links of any SRLG share an endpoint.…”
mentioning
confidence: 99%